Integration Analysis of Transcriptome and Proteome Reveal the Mechanisms of Goat Wool Bending - Liu, Yue; Ding, Yangyang; Liu, Zhanfa; Chen, Qian; Li, Xiaobo; Xue, Xianglan; Pu, Yabin; Ma, Yuehui; Zhao, Qianjun (Frontiers in Cell and Developmental Biology, 2022)
Zhongwei goat is a unique Chinese native goat breed for excellent lamb fur. The pattern of flower spikes of the lamb fur was significantly reduced due to the reduction of the bending of the hair strands with growth. In order to identify protein and transcript dynamic expression of skin and explore the molecular mechanism, we performed the intergrative analysis of transcriptome and proteome of skins from 45-day, 108-day and 365-day goat based on TMT-based quantitative proteomics and RNA-seq methords. In the three comparison groups, the total number of DEPs screened were 356, 592 and 282, respectively. KEGG pathway analysis indicated that DEPs were signifcantly enriched in a set of signaling pathways related to wool growth and bending, such as ECM-receptor interaction, PI3K-Akt signaling pathway, PPAR signaling pathway, protein digestion and absorption, and metabolic pathways. In addition, 20 DEPs abundance of goat skin at three development stages were examined by PRM method，which validated the reliability of proteomic data. Among them, KRT and collagen alpha family may play an important role in the development of goat hair sac and hair bending. COL6A1, COL6A2, CRNN, TNC and LOC102178129 were identified as candidate genes based on combined analysis of transcriptome and proteome data and PRM quantification. Our results identify the differential expressed proteins as well as pathways related to the hair bending of Zhongwei goats and provide a theoretical basis for further revealing the molecular mechanism underlying hair bending of goats.